Formulation and evaluation of in situ herbal gel containing aqueous and methanolic extract of fruits of Quercus infectoria Oliv. for vaginal application - Tiwari, Sarika Sharma; Gupta, Shailesh K.; Dwivedi, Sumeet; Dubey, Raghvendra (Journal of Drug Delivery and Therapeutics, 2018)
Conventional vaginal dosage forms frequently produce leakages and drip. There is a need for the development of innovative vaginal formulation technology that fulfills certain criteria such as desirable product dispersion throughout the vagina, retention for intended intervals, and adequate release of drug. These features can be achieved by the use of bioadhesive based novel delivery systems. In-situ gelation is a process of gel formation at the site of application after the composition or formulation has been applied the site. Formulation and evaluation of one such bioadhesive based novel drug delivery system for an effective and patient friendly use of an antifungal drug to formulated In-situ gel. Quercus infectoria is medicinally important plant grown wildly in India and is useful in the treatment of fungal and microbial infection by tribal’s of India. The plant is used by tribal women to treat vaginal infection as mentioned in folk-lore. Therefore, the present plant as selected to formulate in-situ herbal gel using Quercus infectoria as active ingredients for the treatment of vaginal infection. Keywords: Herbal Gels, Quercus infectoria, bioadhesive, vaginal drug delivery